Exposure time of virgin coconut oil against oral Candida albicans - Tjin, Lui Dwen; Setiawan, Ame Suciati; Rachmawati, Emma (Padjadjaran Journal of Dentistry, 2016)
Introduction: Virgin Coconut Oil (VCO) is an oil which is purely made as a product of the coconut palmand has been used for centuries in the culinary industry and the medical field. Currently, VCO is used widely in medical field due to its effectiveness as antibacterial, antiviral and antifungal properties. Objective of this experimental study was to prove the effectiveness of virgin coconut oil by determining its exposure time at concentration of 25% to inhibit growth of oral Candida albicans. Methode: The research was done by quasi experiment design using the serial dilution method. The exposure time test was performed using a spread plate technique with virgin coconut oil at concentration of 25 % against oral Candida albicans isolated from saliva. Intervals of day 0, 1, 2 and 3 were used. Result: shows that virgin coconut oil inhibited the growth of oral C. albicans cells at day 2. Conclusion: virgin coconut oil with concentration of 25% can inhibit the growth of oral C. albicans with the exposure time of 2 days, which is similar with other antifungals.